Extent of surgical repair and outcomes after surgery for type A aortic dissection - Biancari, Fausto; Fileccia, Daniele; Ferrante, Luisa; Mäkikallio, Timo; Juvonen, Tatu; Jormalainen, Mikko; Mariscalco, Giovanni; El-Dean, Zein; Pettinari, Matteo; Rodriguez Lega, Javier; Pinto, Angel G; Perrotti, Andrea; et al. (BJS open, 2025)
BACKGROUND: Acute Stanford type A aortic dissection is a severe emergency condition that, if left untreated, is associated with a high mortality rate. The extent of surgical repair may impact the outcomes of these patients. METHOD: Patients operated for acute type A aortic dissection from a multicentre European registry were included. Patients were categorized based on the following types of surgical intervention: isolated ascending aortic replacement, ascending aortic replacement with concomitant aortic valve replacement, aortic root replacement, partial or total arch replacement, and partial or total arch replacement with concomitant aortic root replacement. The primary outcome was mortality rate, both in-hospital and at 10 years. Secondary outcomes were acute kidney injury requiring dialysis, neurological complications, a composite endpoint including in-hospital death, neurological complications and/or dialysis, and proximal endovascular or surgical aortic re-operations at 10 years. RESULTS: 3702 patients were included. The adjusted risk of in-hospital mortality was higher in all subsets of patients compared to those who underwent isolated ascending aortic replacement. The adjusted rates of in-hospital mortality ranged from 16.4% (95% c.i. 15.3 to 17.4) among patients who underwent isolated ascending aortic replacement to 27.7% (95% c.i. 23.3 to 31.2) among those who underwent aortic arch and concomitant aortic root replacement. The adjusted risks of neurological complications, renal replacement therapy and of the composite endpoint were significantly higher in patients who underwent partial/total aortic arch replacement. The adjusted risk estimates of 10-year mortality rate were markedly higher in patients who underwent partial/total aortic arch replacement with or without concomitant aortic root replacement. Extensive aortic repair did not significantly reduce the risk of distal or proximal aortic reoperations. CONCLUSION: These findings suggest that, when feasible, limiting the extent of aortic replacement for acute type A aortic dissection may be beneficial in reducing mortality rate and major complications both in the short and long term. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT04831073.
Keywords: Registries; cévy - implantace protéz; Humans; lidé středního věku; registrace; Female; Aged; Aortic Dissection; Acute Kidney Injury; výsledek terapie; senioři; lidé; Europe; reoperace; mortalita v nemocnicích; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; disekce aorty; Treatment Outcome; Blood Vessel Prosthesis Implantation; Hospital Mortality; mužské pohlaví; akutní poškození ledvin; Reoperation; Evropa